PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL AND ANTIOXIDANT PROPERTIES OF INDIGOFERA TINCTORIA L. - Swaminathan, Chandrasekaran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was designed to evaluate the phytochemical composition and antibacterial and antioxidant potential of methanolic leaf and root extracts of Indigofera tinctoria L. Methods: Phytochemical analysis was done using standard methods. The methanolic leaf and root extracts of the plant were tested against Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae, Enterobacter aerogenes, and Salmonella paratyphi B by cup-plate agar diffusion method. The free radical scavenging activities of the methanol extracts of leaves and roots were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Results: Phytochemical screening revealed the presence of carbohydrates, reducing sugars, alkaloids, saponins, phenolic compounds, and flavonoids in methanolic leaf and root extracts. Methanolic leaf extracts of the plant exhibited antibacterial activity against a wide range of bacteria, but the root extracts failed to inhibit the tested bacterial pathogens. The antioxidant activity determination revealed that at 100 Î¼g/ml, methanolic root extracts had the highest antioxidant activity (89.10%) on DPPH free radicals followed by methanolic leaf extracts (46.74%). Conclusion: The results of the present study conclude that the studied plant possesses broad-spectrum antibacterial and antioxidant properties and may act as a potent antioxidant for biological systems susceptible to free radical-mediated reactions. Â 